Hydrogen production by glycerol dry reforming over rhenium promoted Ni-based catalyst supported on Santa Barbara Amorphous 15 (SBA-15) - Nurul Asmawati, Roslan; Nur Nabillah, Mohd Arif; Jessy, Lynn Jaspin; Nurul Aini, Mohamed Razali; Sumaiya, Zainal Abidin (Taylor & Francis, 2019)
This paper presents the glycerol dry reforming (GDR) reaction using rhenium (Re) promoted on Ni-based catalyst supported on Santa Barbara Amorphous 15 (SBA-15) for the production of hydrogen. In this study, the non-promoted (15%Ni/SBA-15) and promoted (3%Re-15%Ni/SBA-15) catalysts were first synthesized using wet impregnation method and their physicochemical characteristics were analyzed with Brunauer–Emmet–Teller (BET), scanning electron microscopy (SEM), X-ray diffraction (XRD), and thermogravimetric (TGA) analyses. Their performances were evaluated in GDR reaction and it was found that 3%Re-15%Ni/SBA-15 exhibited higher glycerol conversion (57%) and hydrogen yield (55%) than 15%Ni/SBA-15 (i.e., 20% glycerol conversion and 18% hydrogen yield). From the GDR study, the highest glycerol conversion (57%) and hydrogen yield (55%) for 3%Re-15%Ni/SBA-15 were obtained at 0.2 g catalyst, 700°C of reaction temperature, and CO2 to glycerol ratio (CGR) of 1:1. The small crystallite size and BET surface area of 3%Re-15%Ni/SBA-15 had successfully reduced the carbon deposition and indirectly contributed to high glycerol conversion and product yield.